Restoration of Decreased T Helper 1 and CD8+ T Cell Subsets Is Associated With Regression of Lymphoproliferative Disorders Developed During Methotrexate Treatment - Saito, Shuntaro; Suzuki, Katsuya; Yoshimoto, Keiko; Kaneko, Yuko; Yamaoka, Kunihiro; Shimizu, Takayuki; Mori, Takehiko; Okamoto, Shinichiro; Kameyama, Kaori; Amano, Koichi; Tamaru, Jun-ichi; Tokuhira, Michihide; et al. (Frontiers in Immunology, 2018)
Background: Lymphoproliferative disorders (LPD), including malignant lymphoma, is a relatively rare but life-threatening complication in RA patients under methotrexate (MTX) therapy. Spontaneous regression of LPD after MTX withdrawal is regarded as a distinct characteristic in part of such LPDs. Objective: The present study aimed to investigate the immunological difference in regressive LPD and persistent LPD. Methods: We studied RA patients who developed LPD during MTX administration (n = 35) and clinically matched controls (n = 35). The time of MTX cessation was defined as week 0, and LPD patients were divided into two groups according to LPD status at week 12: regressive group (n = 22) and persistent group (n = 13). Flow cytometric analysis of whole blood samples and serum cytokine assays were conducted for LPD (n = 10) and control patients (n = 10) at weeks 0, 4 and 12. Results: There was a significant decrease in peripheral lymphocytes and the proportion of T helper 1 cells (Th1 cells), effector memory CD8+ T cells (EMCD8+ T) and Epstein–Barr virus (EBV)-specific CD8+ T cells at the time of LPD diagnosis, and a significant increase after MTX cessation was observed in the regressive group but not in the persistent group. The expansion of Th1 cells and EMCD8+ T cells significantly correlated with an increase in serum interferon (IFN)-γ concentration. Conclusion: Changes in Th1 cells, EMCD8+ T cells and EBV-specific CD8+ T cells, which coincided with an increase in IFN-γ, were significantly different between regressive LPD and persistent LPD after MTX cessation.